The New Guidelines for Japan‐U.S. Defense Cooperation and an Expanding Japanese Security Role. Issue 1 (16th January 2016) - Satake, Tomohiko
Abstract : This article examines the changing role of Japan and its alliance with the United States by focusing on the new Guidelines for Japan‐U.S. Defense Cooperation announced in April 2015. The article focuses particularly on the implications of the 2015 guidelines for a greater regional security role for Japan, including its potential cooperation with the United States and Australia. To do so, it first considers the meaning and roles encapsulated in the Defense Guidelines using two key concepts—"reassurance" and "burden‐sharing." Second, the article discusses how the latest guidelines have increased the U.S. commitment to Japanese defense, while assigning Japan a greater security role in the region. Third, it examines the possibilities and challenges ahead for closer U.S.–Japan–Australia cooperation especially in the South China Sea, and concludes that achieving such a goal depends on how Japan can address its domestic and international issues, including the successful implementation of legal reforms in Japanese security policy.